KEJADIAN PERDARAHAN DAN KELAMIN GANDA PADA EMBRIO PENYU HIJAU (Chelonia mydas) YANG DIDEDAHKAN TERHADAP HERBISIDA PARAKUAT DIKLORIDA - Yetty Yusri Gani; Pipit Pitaloka (BIOTIKA Jurnal Ilmiah Biologi, 2002)
This experiments had been carried out in our laboratory to learn wether paraquat herbisides were responsible to disrupt the developmental profile and sex differentiation of green turtle (Chelonia mydas) embryos. Paraquat dichlorides which were 22; 31; 42; 58 mg/kg of sand weight sprayed to the incubation sand covering fertile eggs for the incubation period between the day 19th (Stage 18) and 43th (Stage 24). Tap water without paraquat also sprayed as control. On the observable embryos were significantly found hemorrhages and gonadal intersex status. Hemorrhages embryos were  60% to 100% occurred in all treated paraquat, while 20% in the control. Statisticaly the hemorrhages were significant (p £ 0,05) in 22; 31; and 42 mg/kg, and highly significant (p £ 0,01) in 58 mg/kg of paraquat, were showed these percentage increasing depend in the given concentration (r = 0,9387). The gonadal intersex of green turtle embryos were signated by well developed both in cortical and medullary as ovary and testicle anlage, and occurred in 31; 42; and 58 mg/kg of paraquat. Since the presence of paraquat had been detected in the allantoic fluid of embryos, ensure that paraquat absorbed into embryos and this herbicides might have lead to the disruption of embryos directly. Key words : Paraquat dichlorides, Green turtle (Chelonia mydas) embryos, hemorrhages, intersex.